STRATEGI PEMASARAN PEDAGANG PASAR TRADISIONAL MENGHADAPI PERSAINGAN dengan PASAR MODERN (Study Kasus Pada Pasar Kemiri Sp. Limun Kota Medan) - Kevin Pradipta Sitepu; Putri Anisa; Jane Olivia Theresia Sitio; Senin Apdi Jeremia Tampubolon (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the marketing strategies implemented by traditional market traders in facing competition from modern markets, specifically at Pasar Kemiri Simpang Limun in Medan City. With the increasing presence of modern retail, traditional market traders are confronted with the challenge of retaining customers and sales turnover. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results indicate that although there is a decrease in the number of consumers, traditional market traders are still able to maintain sales turnover through competitive pricing strategies and a bargaining system favored by consumers. This study also finds that comfort and service quality in modern markets are factors influencing consumer preferences; however, traditional markets still possess their own appeal. The conclusion of this research emphasizes the importance of innovation and adaptation of marketing strategies for traditional market traders to remain competitive in the modern era.